Analisis Pembelajaaran Bahasa Indonesia Menggunakan Kurikulum Merdeka Pada Siswa UPT SD Negeri 183 Tolada - Azizah, Wafiq; Khaltsum, Ummu; Rahayu, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of Indonesian language learning using the Merdeka Curriculum at UPT SD Negeri 183 Tolada. The background of this research is based on the importance of implementing the Merdeka Curriculum, which emphasizes student-centered learning, literacy development, flexibility in differentiated instruction, and the implementation of assessment that has not yet been optimal. This study employed a qualitative approach with a descriptive design. The research subjects consisted of teachers and students, and the data were collected through observation, interviews, and documentation. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques, while data validity was ensured through triangulation. The results of the study indicate that Indonesian language learning using the Merdeka Curriculum at UPT SD Negeri 183 Tolada has been implemented quite well. Teachers have prepared learning plans through teaching modules aligned with Learning Outcomes (Capaian Pembelajaran/CP) and Learning Objectives Flow (Alur Tujuan Pembelajaran/ATP). The learning process is carried out actively, using varied methods, relevant media, and with a fairly high level of student participation.